9. KEKERASAN DALAM RUMAH TANGGA (KDRT) DALAM PERSPEKTIF NEGARA, BUDAYA DAN AGAMA - Taufiq, Ahmad (Faculty of Social and Political Sciences Diponegoro University, 2008)
Violence in the private area consist of physical violence, psychological violence, sexual violence and out of family. Each violence cause impact especially phychological impact of victim. The implementation of UU No. 23 tahun 2004 about elimination of violence in private area has not been effectively done, because there are still many violence of private area cases happened every year. This problem need serious concern and coordination of government and others element involved. The solution to prevent woman and children from this violence are by socializing the act, by promoting idea against patriarchy culture and by given the right interpretation and perception about the position women in Islam.